2003
DOI: 10.1128/aac.47.10.3240-3246.2003
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils as Components of a Diet-Based Approach to Management of Helicobacter Infection

Abstract: An increased density of Helicobacter pylori in the gastric mucosa can be associated with more severe gastritis and an increased incidence of peptic ulcers. Therefore, people with asymptomatic gastritis would certainly benefit from a nutritional approach to help them manage the infection and therefore decrease the risk of development of associated pathologies. We analyzed the activities of 60 essential oils against H. pylori P1 and identified 30 oils that affected growth, with in vitro inhibition zones ranging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
83
1
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 18 publications
4
83
1
6
Order By: Relevance
“…H. pylori is susceptible to several essential oils, of which cinnamon bark oil and savory oil were the most effective bactericial inhibitors, with the minimum bactericidal concentration for each oil in a liquid medium equal to1 g/L at 1 hour and 0.04 g/L at 24 hours (39). Many of the essential oils with positive bactericidal activity were effective not only against the P1 strain, but other H. pylori strains as well, including a strain resistant to the two drugs which are part of current anti-H. pylori therapies (39). Garlic has been associated with low rates of peptic ulceration and reduced risk for gastric cancer in epidemiologic studies, yet when garlic oil capsules were given to patients with dyspepsia related to H. pylori in a pilot test, the garlic oil at the dose selected based on in vitro studies (4 mg garlic oil capsule with a meal four times per day for 14 days) did not eradicate or suppress H. pylori (47).…”
Section: Health Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…H. pylori is susceptible to several essential oils, of which cinnamon bark oil and savory oil were the most effective bactericial inhibitors, with the minimum bactericidal concentration for each oil in a liquid medium equal to1 g/L at 1 hour and 0.04 g/L at 24 hours (39). Many of the essential oils with positive bactericidal activity were effective not only against the P1 strain, but other H. pylori strains as well, including a strain resistant to the two drugs which are part of current anti-H. pylori therapies (39). Garlic has been associated with low rates of peptic ulceration and reduced risk for gastric cancer in epidemiologic studies, yet when garlic oil capsules were given to patients with dyspepsia related to H. pylori in a pilot test, the garlic oil at the dose selected based on in vitro studies (4 mg garlic oil capsule with a meal four times per day for 14 days) did not eradicate or suppress H. pylori (47).…”
Section: Health Effectsmentioning
confidence: 99%
“…Liu and Nakano postulated that these differences may have been related to use of dried garlic powder in their study compared to other studies which relied on other forms of garlic (41). Essential oils extracted from herbs and spices have displayed varying bactericidal activity when compared to the known antimicrobial activity of their primary constituents, which indicates there may be unknown minor components in the essential oils with antimicrobial activity, or there may be synergistic or antagonistic effects between all the bioactive compounds combined (39,43). Yano et al measured the inhibitory action of several herbs and spices on E. coli and V. parahaemolyticus and found that gram positive bacteria which form spores appear to be more sensitive to herbs and spices (44).…”
Section: Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies also found that the most pathogenic gut bacteria, E. coli O157 : H7 (Burt & Reinders, 2003;Delaquis et al, 2002), Salmonella typhimurium (Si et al, 2006), Clostridium perfringens (Ouwehand et al, 2010), Campylobacter jejuni (Anderson et al, 2009) and Helicobacter pylori (Bergonzelli et al, 2003) are inhibited by EO in vitro. The aim of the present study was to compare the effects of a range of EO and EO compounds on human pathogenic and commensal intestinal bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to ephedra, it contains alkaloids that are adrenergic agonists and is often incorporated into supplements designed to aid in weight loss (Haaz et al 2006). It was confirmed that its essential oil has an antibiotic effect against Helicobacter pylori (Bergonzelli et al 2003). Novel triterpenoid from C. aurantium L. also possesses chemopreventive properties against human colon cancer cells (Gougeon et al 2005).…”
Section: Introductionmentioning
confidence: 89%